Foresight Study on the Adoption of Artificial Intelligence (AI) in Employee Wellness Program in Malaysia - Arultas, Kishalini A/P; Wahab, Eta (Research in Management of Technology and Business, 2025)
Artificial Intelligence (AI) technology makes it possible for machines and computers to resemble human intelligence and problem-solving skills. Artificial intelligence in employee wellness programs is the proper use of corporate wellness software and technology, which has become essential to technological advancements, creating a solid basis in a wide range of industries. Few studies have been conducted on AI adoption in Employee Wellness Programs in Malaysia. Therefore, this research intends to identify the issues, challenges, and trends of AI in employee wellness programs, study the key drivers of AI in employee wellness programs in Malaysia, and identify the future image of AI in employee wellness programs in Malaysia. 384 questionnaires were distributed to the employees in HRM in Malaysia, with a response rate of 60%. The study found that wellness technology, accessibility, and engagement have the highest impact and uncertainty. Four scenarios were proposed at the end of the study. The four scenarios were the thriving of AI, the sluggishness of AI technology, the scarcity of AI, and the scepticism of AI technology